Social Evaluation Through Notional Choice - Alexander, Sidney S. (Quarterly Journal of Economics, 1974)
I. Introduction, 597. — II. The underlying metaphysics, 600. — III. A notional mechanism for social evaluation, 603. — IV. The theory is utilitarian, 606. — V. The conflation problem, 609. — VI. Specification of the good, 618. — VII. Pluralism in welfare standards, 621.